Building the Census Bureau Index of Economic Activity (IDEA) - Jose Asturias; William R. Bell; Rebecca Hutchinson; Tucker S. McElroy; Katherine J. Thompson (Data Science in Science)
The Census Bureau Index of Economic Activity is constructed from 15 of the Census Bureau’s primary monthly economic indicators to provide a single time series reflecting the variation over time in the whole set of component series. The component series provide monthly measures of activity in retail and wholesale trade, manufacturing, construction, international trade, and business formations. The index applies the method of principal components analysis (PCA) to the time series of monthly growth rates of the seasonally adjusted component series, after they are standardized to have mean zero and variance 1. The index is published every business day, and so is updated whenever a new monthly value is released for any of its components. Since the monthly release dates vary across the components, series that are one month behind are nowcast for the current index month using a multivariate autoregressive model to provide an index that is conceptually consistent over time. This paper discusses the input series to the index, the construction of the index by PCA, and the nowcasting procedure. We then examine some properties of the index and its relation to quarterly U.S. Gross Domestic Product and to some monthly non-Census Bureau economic indicators.